Effects of surface wettability on pool boiling of water using super-polished silicon surfaces. (December 2018) - Mohammadi, Niloofar; Fadda, Dani; Choi, Chang Kyoung; Lee, Jungho; You, S.M.
Highlights: Study of the effects of surface wettability on pool boiling of water with super-polished silicon surfaces. The impact of wettability is isolated from roughness. Development of integrated resistance-temperature detector and heater. Experimental identification of a trend in increasing the critical heat flux value of pool boiling for more wettable surfaces. Abstract: Pool boiling is an efficient cooling technique as a phase change heat transfer mode. Improvement of the boiling performance by postponing the surface dry-out point and increasing the critical heat flux is often necessary for assuring safe performance in many applications involving high heat fluxes. Recently, relevant surface modifications have become an attractive, yet practical approach for enhancing boiling performance. These modifications are implemented either by manipulating the surface wettability characteristics or imposing roughness onto the surface. In most cases, the mentioned modifications are dependent, where variation in one is accompanied by a change to the other. This study aims at the sole impact of surface wettability on the pool boiling performance with super-polished silicon surfaces with different wettability characteristics prepared by chemical vapor deposition and sputtering. Pool boiling experiments are conducted using these surfaces where the heat supply and temperature measurement were performed via an integrated state-of-the-art resistance-temperature detector and heater. The experimental results show a trend in increasing the critical heat flux value of the pool boiling for more wettable surfaces and quantitatively define a low limit for the critical heat flux. Moreover, nucleation and bubble behavior are also studied at incipience.